Analisis Pengaturan Pajak Karbon di Indonesia Ditinjau dari Prinsip Pencemar Membayar (Polluter Pays Principle) (Studi Komparatif dengan Negara Singapura): Studi Komparatif dengan Negara Singapura - Alif Pratama; Niken Wahyuning Retno Mumpuni (Jurnal Hukum Lex Generalis, 2025)
Carbon tax aims to reduce greenhouse gas emissions and promote environmental sustainability. This study compares carbon tax policies in Indonesia and Singapore, which are considered successful through consistent regulation and industry involvement. To analyze the legal aspects, this study uses a normative juridical method with a polluter pays principle approach. Although it has the potential to increase state revenue and encourage environmentally friendly technology, this policy faces challenges in the form of low public understanding and industry resistance. Education, inclusive policies, and international cooperation are the keys to the successful implementation of carbon tax in Indonesia.